Artificial Intelligence and Landscape Architecture: The Aesthetic and Sustainable Fabric of The Future (Ecological Perspective, 2024)
This article examines the impact of artificial intelligence on the field of landscape architecture and discusses its potential role in shaping aesthetic and sustainable designs in the future. It addresses the contributions of AI technologies to big data analytics, environmental sensitivity, sustainability, and functional landscape designs. The study highlights the potential of artificial intelligence to provide innovative and sustainable solutions within landscape architecture.
Keywords: Artificial intelligence; Data analysis; Environmental sensitivity; Landscape architecture; Sustainability